The impact of orthognathic surgery on quality of life in oral clefts - Feitosa, Mariana Chaves Petri (2020)
The aim of this study was to evaluate the relationships between individual, environmental, biological factors, and oral health-related quality of life (OHRQoL) in patients with cleft lip and palate (CLP) before orthognathic surgery and 6 months after surgery. The study was conducted involving 69 adults with unilateral and bilateral CLP under orthodontic treatment. Interviews and oral examinations were carried out before orthognathic surgery (baseline) and 6 months after orthognathic surgery to collect demographics (age and sex), psychological well-being, dental clinical measures (dental caries, malocclusion), social support, social networks, and socioeconomic status (family income and education) and OHRQoL (OHIP-14). Structural equation modelling was used to estimate direct and indirect associations between the variables. Reduction of malocclusion between baseline and follow-up directly predicted poor OHRQoL at follow-up ( = 0.02) whereas increase in psychological well-being between baseline and follow-up was associated with better OHRQoL at follow-up ( = -0.07). Poor OHRQoL at baseline predicted worse OHRQoL at follow-up ( = 0.28). Malocclusion at baseline was indirectly linked to poor OHRQoL at follow-up via OHRQoL at baseline, and via reduction of malocclusion ( = 0.02). Age and OHRQoL at baseline mediated the link between dental caries OHRQoL at T1. The short followup period of 6 months after orthognathic surgery, the use of a non-specific questionnaire to assess OHRQoL in patients with CLP and the sample size should be acknowledged as possible limitations of the present study. Orthognathic surgery positively impacted the quality of life. Better psychological outcomes predicted a better OHRQoL after orthognathic surgery in this population. On the other hand, a greater decrease in the severity of malocclusion can induce a worse quality of life in the first post-surgical six months